Financial leverage usage for active management of the investment portfolio - Aleksandras Vytautas Rutkauskas (Business: Theory and Practice, 2010)
The analysis of the portfolio theories was carried out in the article. H. Markowitz theory of an optimal portfolio formation was briefly described, the process of the portfolio selection was discussed, the basic corrections, improvements, development and application of the theory suggested by the scientists were named. With reference to the literature analysis the most suitable portfolio theory was chosen for further development, aiming at the application of the theory to active portfolio management using the financial leverage. The basic limitations of the chosen theory were evaluated in order to apply it to the subject of research, specific development solutions were suggested and, on the grounds of them, the adjusted efficient set was proposed. An empirical research was carried out, validating the expedience of the financial leverage usage when actively managing the investment portfolio, and evaluating the intensity of the financial leverage usage. Built  on the results of the research,the efficient set which was suggested in the theoretical-hypothetical part of the study was adjusted.